Multiplex profiling of 16 immune checkpoints identifies novel serum biomarker panels for breast cancer detection and TNBC stratification: A case-control study - Mouna Stayoussef; Azza Habel; Weili Xu; Mariem Bessaad; Hanen Bouaziz; Mouna Ayadi; Wassim Y. Almawi; Anis Larbi; Besma Yacoubi-Loueslati (PLoS ONE, 2026)
Background Immune checkpoints (ICs) are key regulators of anti-tumor immunity, yet their diagnostic potential as blood-based biomarkers in breast cancer (BC) remains insufficiently characterized. Comprehensive serum profiling using multiplex immunoassays may enable minimally invasive detection and molecular stratification, particularly for triple-negative breast cancer (TNBC). Methods Serum samples from 88 treatment-naïve BC patients and 49 age-matched controls were analyzed using a 16-analyte MILLIPLEX® immuno-oncology panel. Six co-inhibitory and ten co-stimulatory IC proteins were quantified. Diagnostic accuracy was assessed using ROC curves and logistic regression. Associations with TNBC subtype, chemotherapy response, and 6-month progression-free survival (PFS) were evaluated. Results Seven immune checkpoint proteins (LAG-3, BTLA, CD80, GITRL, CTLA-4, GITR, TLR-2) showed significant differential expression between BC patients and controls. A seven-protein panel demonstrated high diagnostic accuracy (AUC = 0.89; sensitivity 83%; specificity 86%), surpassing CA15−3 and CEA. TNBC patients exhibited a distinct eight-protein signature, with TIM-3, CTLA-4, and CD28 independently associated with TNBC classification. Elevated baseline TIM-3 and PD-L1 were associated with chemotherapy resistance and shorter PFS. Conclusions Comprehensive serum IC profiling identified biomarkers with strong diagnostic and subtype-discriminatory potential. These minimally invasive panels show potential for BC detection and TNBC stratification, pending validation in prospective and longitudinal studies. Validation in larger, multi-center cohorts is warranted.